Association of Body Mass Index with The Risk Of Gout Arthritis in Male and Female with Underweight, Normal Weight, Overweight, Obese - Raharjo, Slamet; Andiana, Olivia (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The current study aims to analyze the correlation between body mass index (BMI) in underweight, normal weight, overweight, obese with the risk of gout arthritis in male and female adolescents in Malang. We conduct a correlational with a cross-sectional study approach. A total of 101 adolescents consisting of 59 men and 42 women, aged 16 – 23 years, with body mass index in categories underweight, normal weight, overweight, and obese are participated in this study. Uric acid levels were measured using Easy Touch (Easy Touch, Hsinchu, Taiwan) with a concentration unit of mg/dL, while BMI was calculated by dividing body weight (BW) (kg) with body height (BH) (m2). Pearson's correlation coefficient was used to analyze the correlation between BMI and uric acid levels. The results showed that the mean BMI was underweight (17.64 ± 0.26 kg/m2), normal weight (21.94 ± 1.33 kg/m2), overweight (25.81 ± 0.51 kg/m2), obese (29.92 ± 2.80 kg/m2), and levels of uric acid (6.09 ± 1.61 mg/dL) with (r = 0.838; p ≤ 0.001). Based on the results of the study, it was concluded that there was a positive correlation between BMI and uric acid levels. BMI showed a strong positive correlation with uric acid levels